Where You Export Matters: Measuring Uncertainty in Turkey's Export Markets - Jianchun Fang; Giray Gozgor; Sercan Pekel (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Using data from the World Uncertainty, World Trade Uncertainty, and World Pandemic Uncertainty indices for 142 countries, this paper introduces three new indicators for measuring uncertainty in Turkey's export markets from the first quarter of 1996 to the first quarter of 2020. The indicators measure uncertainty in Turkey's export destinations. After introducing three indicators of uncertainty for export markets, we investigate their effects on economic growth. We find that all uncertainty indicators are negatively related to economic performance. Specifically, an increase in uncertainty in export destinations leads to a slower growth rate of up to two quarters. Pandemic-induced uncertainty negatively affects economic growth only at the higher quantiles. We also discuss potential implications.
Keywords: F14; F43; D81; C21; 330; export market diversification; economic policy uncertainty; trade policy uncertainty; Covid-19 uncertainties; developing economics; quantile regressions